ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA BANJIR DI KABUPATEN BUTON UTARA - Wa Ode Yuli Indriani; Sartiah Yusran; Nani Yuniar (NHM PRESS, 2022)
Disaster events in Indonesia are dominated by hydrometeorological activities, and 75% of the total disaster events are floods. Preparedness is the most critical phase in the range of disaster management which can cause chaos, worsen the victim's condition, and claim the victim's life if not prepared optimally. This study aims to analyze factors related to community preparedness in dealing with floods in North Buton Regency, namely in 5 sub-districts/villages, which are prone to floods with a high category, namely Wacu Laea Village, Lapandewa Sub-District, Lambale Sub-District, Kambowa Village and Desa Lahumoko. The method used is cross-sectional with a population of all people aged 17 years and over and are in flood-prone areas in North Buton Regency, namely 2,027 people. The number of respondents was 254 people selected by purposive sampling. Bivariate analysis in this study used the Chi-Square test, while multivariate analysis used the binomial logistic regression test. The results of the Chi-Square test show that there is a significant relationship between knowledge (p=0.02), attitude (p=0.00), training experience (p=0.00) and infrastructure (p=0.00) and community preparedness in dealing with flood disasters in the district. North Buton. Meanwhile, the results of the logistic regression test explain that attitude is the factor most related to community preparedness in dealing with floods with Exp(B) = 18.25. The conclusion of the study is that knowledge, attitude, training experience and infrastructure are related to community preparedness in dealing with flood disasters